PERBEDAAN KONTROL DIRI REMAJA DALAM LINGKUNGAN SOSIAL DI DESA KALI SELATAN KABUPATEN MINAHASA BERDASARKAN KARAKTERISTIK JENIS KELAMIN - Millinia J. Tambayong; Meike E. Hartati; Stevi B. Sengkey (Program Studi Psikologi Universitas Negeri Manado, 2022)
The purpose of this study was to determine the existence of differences in self-control in adolescents in Kali Selatan Village, Kab. Minahasa Based on Gender Characteristics. The research method uses quantitative research methods with comparative methods. The subject of this study used 87 teenagers in Kali Selatan Village aged 12-15 years. The research instrument for the self-control scale is the research scale from Averill with 23 items. The research was tested using a comparative test. Based on the results of the study, it showed that there was no difference in self-control between male and female adolescents with a mean male sex of 71.8333 with an N of 36 and a mean female sex of 72.1569 with an N of 51 with a mean difference = -32353. This shows that Ho is accepted which reads